Manifest Invalidity of Marriage as a Requirement for the Application of Short Procedure - Leszczyński, Grzegorz (Prawo Kanoniczne, 2025)
The shortened process, which is undoubtedly an extremely innovative assumption of Pope Francis’ reform, constitutes the greatest challenge for church tribunals. This process can be carried out after meeting two basic requirements: the request has been submitted by both spouses or by one of them with the consent of the other; circumstances relating to facts or persons are cited, supported by testimony or documents, which do not require a more detailed examination or investigation and clearly indicate invalidity (can. 1683 CIC). The possibility of using the abbreviated process therefore seems to be obvious only in obvious situations. This article is an attempt to show the obviousness of the invalidity of marriage as one of the requirements for applying the shortened process.